2016
DOI: 10.15288/jsad.2016.77.723
|View full text |Cite
|
Sign up to set email alerts
|

Amount of Televised Alcohol Advertising Exposure and the Quantity of Alcohol Consumed by Youth

Abstract: ABSTRACT.Objective: Although studies demonstrate that exposure to brand-specific alcohol advertising is associated with an increased likelihood of youth consuming particular brands, the relationship between quantity of brand-specific advertising exposure and quantity of brandspecific consumption has not been firmly established. Method: Using the Alcohol Brand Research Among Underage Drinkers (ABRAND) national sample of 1,031 young drinkers (ages 13-20), this study examined the relationship between their aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 16 publications
2
18
1
Order By: Relevance
“…For example, a British study reported positive associations between seeing alcohol advertising on television, in movies, and in magazines with past-month drinking frequency ( Gunter et al, 2009 ). Similarly, two American studies found positive associations between seeing alcohol advertising on television, assessed using ad stock data, and past-month brand-specific consumption frequency ( Ross et al, 2015 ) and quantity ( Naimi et al, 2016 ). As with other alcohol use outcomes, many of the studies also found null associations for other media types or when using different measures of exposure.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…For example, a British study reported positive associations between seeing alcohol advertising on television, in movies, and in magazines with past-month drinking frequency ( Gunter et al, 2009 ). Similarly, two American studies found positive associations between seeing alcohol advertising on television, assessed using ad stock data, and past-month brand-specific consumption frequency ( Ross et al, 2015 ) and quantity ( Naimi et al, 2016 ). As with other alcohol use outcomes, many of the studies also found null associations for other media types or when using different measures of exposure.…”
Section: Resultsmentioning
confidence: 87%
“…Data were collected from 1980 to 2015, and samples ranged from 89 to ∼63,000 participants. Of the studies in the review, 11 used objective measures of alcohol marketing exposure (e.g., ad stock; Naimi et al, 2016 ) compared with 27 studies that relied only on perceived exposures (e.g., recalling ads; McClure et al, 2013b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A smaller number of studies has assessed whether the quantity of advertising exposure is associated with the total quantity of alcohol consumed by underage youth, and they too have found a positive relationship between past-year exposure to advertising and the total quantity of alcohol consumed in the past 30 days, even after consumption of nonadvertised brands was controlled for ( Naimi et al, 2016 ; Snyder et al, 2006 ). One additional study surveyed a cohort of adolescents over 2 years and found that awareness of marketing at baseline was associated with an increased frequency of alcohol use at follow-up ( Gordon et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%